Effect of graphene nanoplatelets structure on the properties of acrylonitrile–butadiene–styrene composites. (16th November 2017) - Dul, S.; Fambri, L.; Merlini, C.; Barra, G.M.O.; Bersani, M.; Vanzetti, L.; Pegoretti, A.
Abstract : In this study, the effects of various types of commercial graphene nanoplatelets (XG Sciences xGnP M5, C300, C500, and C750) on the thermal, electromagnetic shielding (EMI SE), electrical and mechanical behavior of an acrylonitrile–butadiene–styrene (ABS) copolymer matrix were investigated. The selected nanofillers were characterized and compared in term of surface area, different oxygen content, dimension and density (X‐ray photoelectron spectroscopy, scanning electron microscopy, and helium pycnometry). Graphene nanoplatelets were dispersed in ABS by direct melt compounding at 2, 4, and 8 wt%. Melt flow index (MFI) values almost linearly decreased with all the type of xGnPs, especially with the highest surface area nanofiller (C750). Moreover, EMI SE of neat ABS was improved from −0.7 dB to −2.5 dB (increase more than 3 times) for xGnP (C300, C500, and C750) and to −6.2 dB (increase about 9 times) for xGnP‐M5, in agreement with proportional reduction of electrical resistivity. xGnP‐M5 also resulted in being most effective in enhancing the tensile modulus which improved up to 64%, while a maximum increment of about 20% was obtained with the others xGnP nanoparticles. However, yield stress slightly decreased for xGnP‐M5 (about −9%) and remained fairly constant for others nanofillers. Halpin–Tsai model used to predict the tensile modulus of the nanocomposites suggested that graphene nanoplatelets were randomly oriented in the ABS matrix in a three‐dimensional (3D) manner. POLYM. COMPOS., 40:E285–E300, 2019. © 2017 Society of Plastics Engineers